2021
DOI: 10.38053/acmj.982137
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of the implementation of magnesium and ascorbic acid on myocardial ischemia-reperfusion in open heart surgery

Abstract: Aim: This study aimed to investigate the combined effects of magnesium (Mg) and high dose ascorbic acid on cardiac ischemia-reperfusion (IR) injury. Material and Method: This study was performed on 45 patients that were scheduled for coronary artery bypass graft (CABG) operations. The patients were divided into three equal groups. Group C received 50 mg/kg ascorbic acid; Group CM received the same dose of ascorbic acid plus 30 mg/kg Mg; Group K received neither ascorbic acid nor Mg. At various times duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…1 ). Four trials were excluded due to suspected data duplication [ 37 , 38 ], unclear troponin-related outcome [ 39 ] and poor data reporting in general [ 40 – 43 ]. Seven trials were included in the meta-analysis of which four trials reported the changes of TnI and five of CKMB (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Four trials were excluded due to suspected data duplication [ 37 , 38 ], unclear troponin-related outcome [ 39 ] and poor data reporting in general [ 40 – 43 ]. Seven trials were included in the meta-analysis of which four trials reported the changes of TnI and five of CKMB (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the combined effects of magnesium (Mg) and high-dose AA on cardiac Ischemia Perfusion (IP) damage were investigated; it was determined that to reduce IP, Mg with a high dose of AA can be effective in patients undergoing heart surgery, and it is effective to improve the disease outcomes (60,92).…”
Section: Humanmentioning
confidence: 99%